2010
DOI: 10.1152/ajpendo.90575.2008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise maintains euglycemia in association with decreased activation of c-Jun NH2-terminal kinase and serine phosphorylation of IRS-1 in the liver of ZDF rats

Abstract: . Exercise maintains euglycemia in association with decreased activation of c-Jun NH2-terminal kinase and serine phosphorylation of IRS-1 in the liver of ZDF rats. Am J Physiol Endocrinol Metab 298: E671-E682, 2010. First published December 8, 2009 doi:10.1152/ajpendo.90575.2008.-Stress-activated systems and oxidative stress are involved in insulin resistance, which, along with ␤-cell failure, contribute to the development of type 2 diabetes mellitus (T2DM). Exercise improves insulin resistance and glucose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 96 publications
3
24
0
Order By: Relevance
“…All but two exercise studies (23,44) in male ZDF rats have used forced treadmill running or swimming. During forced exercise, often conducted during the lights-on cycle, animals experience severe psychological stress and disruption of the normal circadian rhythm of the hypothalamic-pituitaryadrenal (HPA) axis (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All but two exercise studies (23,44) in male ZDF rats have used forced treadmill running or swimming. During forced exercise, often conducted during the lights-on cycle, animals experience severe psychological stress and disruption of the normal circadian rhythm of the hypothalamic-pituitaryadrenal (HPA) axis (12).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to investigate the biochemical basis of the effects of physical activity on islet function in ZDF rats in which diabetes is prevented by voluntary running in wheel cages (23,44). Particular focus was placed on whether preserved ␤-cell performance in exercised ZDF rats could be linked to the compensatory pathway of enhanced GL/FA cycling similar to what was observed in compensating islets of ZF rats.…”
mentioning
confidence: 99%
“…However, the mechanisms underlying the age-related decline in β-cell glucose-stimulated insulin release (GSIR) are unknown. Previous studies have suggested that oxidative stress-related β-cell apoptosis and the inhibition of proliferation are associated with β-cell dysfunction and the development of T2DM (Kiraly et al 2010;Harmon et al 2009). Recent studies have shown a reduction in β-cell proliferation and increased sensitivity to apoptosis triggers in elderly individuals (Rankin and Kushner 2009;Maedler et al 2006;Tschen et al 2009;Krishnamurthy et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…During volitional exercise, in association with improvement in glycemia, we also observed decreased circulating markers of inflammation and oxidative stress [circulating IL-6, haptoglobin, MDA levels, and hepatic protein oxidation, phosporylated JNK (pJNK)]. Ser 307 -phosphorylated IRS-1 and PEPCK were also reduced in the liver of exercised rats (103). During each bout of exercise, plasma corticosterone increased, but, due to adaptation, basal cortisone is decreased.…”
Section: Battle To Establish Beneficial Effects Of Exercise and Some mentioning
confidence: 64%